Effectiveness of using Scrapbook Media on Learning Outcomes of Fine Arts Students Class VIII SMP Negeri 2 Barant - Maharani Putri Arum; Abd Kahar; Muhammad Takdir (International Journal of Sustainable Applied Sciences, 2024)
The Scrapbook media comes from the English " scrap " which means leftovers, scraps and " book " means book. According to (Zuraini & Nurhayati, 2021) which is packaged in book form by combining various pieces of images as well as explanations, it is hoped that it will attract attention to the use of scrapbook media on the results. studying fine arts students in class VIII SMP Negeri 2 Baranti. This research is quasi experimental with a one group pretest post test design . The population of this study was the entire class VIII of SMP Negeri 2 Baranti, totaling 76 people. The sample was determined using random sampling technique. The sample for this research was 27 students in class VIII.c, which was carried out using a test method in the form of multiple choices and questionnaires to measure student learning outcomes, both completeness in learning and punctuality in receiving material. The results of the research show that there is effectiveness in using scrapbook media on the learning outcomes of class VIII fine arts students at SMP Negeri 2 Baranti. This is shown from the results of the paired sample T-test pretest and posttest data on student learning outcomes. obtained a significance value . Based on the results of this research which have been analyzed, then it is obtained average value M x = 85 .00 > M y = 66.48. So it can be concluded that this research shows that there is effectiveness in using Scrapbook media on student learning outcomes.